Study on low pressure adsorption of biomethane from biogas by coal activated carbon - Wassana Kamopas (2018)
© School of Engineering, Taylor’s University. A study on low pressure adsorption of biomethane purified from biogas by a commercial coal activated carbon (AC) was carried out. The adsorption mechanisms of biomethane at 80 and 90% CH4concentration were considered by Langmuir model and Dubinin-Astakhov model. The lower biomethane concentration was better adsorbed since the activated carbon gave higher affinity for CO2than that for CH4. By Langmuir model, the limiting uptake of biomethane on the activated carbon (qmax) and the Langmuir’s constant (KL) increased with the decrease of the AC temperature. The value of qmaxfor 80% biomethane adsorption was in a range of 4.80-5.06 mmol/g(AC)compared with a range of 2.98-3.23 mmol/g(AC)for 90% biomethane adsorption. The value of KLwas in a range of 0.37-0.43 MPa-1. For Dubinin-Astakhov equation, the structural heterogeneity parameter (n) for the coal ACs was investigated and found to be 1.48. The isosteric heat of adsorption for 80 and 90% biomethane were in a range of 5.56-9.76 kJ/mol.